Law and economics - Cooter, Robert; Ulen, Thomas (Boston Pearson Addison Wesley, 2004)
Law and Economics have become central organizing philosophies in U.S. legal education. With the Fourth Edition of their best-selling text, Cooter and Ulen continue to provide students with a clear method for applying economic analysis to the study of legal rules and institutions. Following an overview of economic tools for law students and legal analysis tools for economics students, paired chapters offer a combination of clear theoretical analysis supported by practical application. Economic theories in five core areas of the law are used to explain and analyze topics, illustrating how microeconomic theory can be used to increase understanding of the law and improve public policy.
Keywords: Luật học